The Syntax Analysis of Averb of Manner Found in the Novel “the Wonderful Wizard of OZ” (e-Journal of Linguistics, 2023)
This research paper entitled “The Syntax Analysis of Adverb of MannerFound in the Novel “The Wonderful Wizad of Oz”. This research studyaimed to analyze the form of adverb of manner and its positions ofadverb of manner found in the data source. This research study used thetheory proposed by Brown and Miller (1991) in analyzing the treediagram of adverb of manner and it was supported by other theories inanalyzing the form and the position in adverb of manner found in thestructure. Library research was the method used in collecting the data asthe researcher read the data source before getting data in adverb ofmanner. The method that was used in analyzing data was qualitativemethod. The data were taken from the novel entitled “The WonderfulWizad of Oz” that was written by W.W Denslow. The researcher of thisstudy found that there was one form of adverb of manner found in thenovel entitled “The Wonderful Wizad of Oz”. Adverb of manner foundin the data source was an adjective followed by ly- suffix. Therewas one adverb of manner placed in the initial position and eightadverbs of manner placed in final position. They were adverb ofmanner that could be filled in the sentence structure in the form ofadverb of manner
Keywords: Adverb of Manner; Syntax Analysis; Sentence Structure